Neuroinflammation Quantification for Spinal Cord Injury. (25th September 2018) - Amo‐Aparicio, Jesús; Martínez‐Muriana, Anna; Sánchez‐Fernández, Alba; López‐Vales, Rubèn
Abstract: Spinal cord injury (SCI) leads to irreversible devastating neurological disabilities. Accumulated evidence in the literature indicates that the inflammatory response that occurs in the spinal cord following injury contributes importantly to spread tissue damage to healthy regions adjacent to the lesion site, and consequently, to increase neurological deficits. Therefore, targeting inflammation could lead to the development of new therapies to prevent tissue damage and neurological impairments after SCI. Inflammation is regulated, in part, by the expression of pro‐inflammatory and anti‐inflammatory cytokines synthesized, mainly, by glial cells. Hence, methodologies that could ease the quantification of multiple cytokines and immune cells from spinal cord tissue samples are needed to assess the potential of new anti‐inflammatory therapies. In the present unit, we describe how to induce contusion injuries in the mouse spinal cord, as well as, two useful methodologies to assess neuroinflammation in lesioned spinal cord tissue samples. © 2018 by John Wiley & Sons, Inc.